A New Si/TiO2/Pt p-n Junction Semiconductor to Demonstrate Photoelectrochemical CO2 Conversion. (10th December 2015) - Guaraldo, Thaís Tasso; Brito, Juliana Ferreira de; Wood, David; Zanoni, Maria Valnice Boldrin
Graphical abstract: Abstract: This work presents a new Si/TiO2 /Pt p-n junction semiconductor prepared by sputtering, chemical vapor deposition (CVD), photolithography and lift-off techniques. XRD, EDS, FE-SEM, diffuse reflectance (DRS) and photocurrent vs potential curves had been used for semiconductor characterization. The material was designed for high porosity and uniformity of both TiO2 and Pt deposits; both TiO2 anatase phase formation and Pt presence were confirmed. This semiconductor has a characteristic of high light absorption in the ultraviolet and visible regions. A good photocurrent response for the cathodic region was obtained in a CO2 saturated solution (−1.0 mA under −0.8 V and UV–vis light), confirming electron-hole pair formation and CO2 electron scavenging. A small Si/TiO2 /Pt electrode (1 × 1 cm) was employed in photoelectrocatalytic CO2 reduction, forming methanol (0.88 mmol L −1 ), ethanol (2.60 mmol L −1 ) and acetone (0.049 mmol L −1 ) as products reaching a Faradaic efficiency of 96.5%. These results had been obtained under the following optimal experimental conditions: 0.1 mol L −1 NaHCO3, pH 8 saturated with CO2, 125 W UV–vis irradiation (from 250 to 600 nm) and −0.8 V applied potential. Suitable charge transfer mechanisms in the electrode surface, and products formation after CO2 reduction, are proposed.